Top classic citations in pancreatic cancer research - Li, Qiang (World J Surg Oncol, 2016)
BACKGROUND: The number of times that articles are cited by is widely used to evaluate the impact of an article or an individual author has on its scientific community. This bibliometric analysis aimed to explore the top classic citations in pancreatic cancer (PC) research. METHODS: A computerized literature search was conducted using the database, the Science Citation Index Expanded. The top 100 highly cited articles were included and further analyzed. RESULTS: The most cited article had 3,032 citations, with a mean of 626 citations per paper. These highly cited articles were published in 37 journals, led by Cancer Research (15 articles). Of the 100 articles, 40 were observational studies, 36 dealt with basic science, and 14 were randomized controlled trials. These articles came from 11 countries, with the USA contributing 79 articles. Fifty-one institutions produced these 100 citation classics, led by Johns Hopkins University (20 articles). Twenty-seven persons authored two or more of the top-cited articles, led by Kern SE (6) and Yeo CJ (5). CONCLUSIONS: This analysis of the top highly cited articles allows for the recognition of major advances in PC research and gives a historic perspective on the progress of this specialty of PC research.